2005
DOI: 10.1139/b05-048
|View full text |Cite
|
Sign up to set email alerts
|

Age, stand density, and tree size as factors in root and basal grafting of lodgepole pine

Abstract: This study investigated stand factors associated with the rate of root graft formation in lodgepole pine stands. Forty plot areas, each containing 10 trees, were excavated in pure, even-aged pine stands in western Alberta. Exposed root systems were examined for grafts and various stand measurements were recorded at each plot. Results indicate that the number of grafts per square metre is controlled by plot tree density and tree diameter. Also, the percentage of grafted trees increased with both increasing tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 6 publications
4
27
1
Order By: Relevance
“…1 in Fraser et al (2006)). An attenuated effect of budworm outbreak in grafted trees supports the hypothesis that common functioning of genetically distinct individuals can overcome the death of weaker trees (Basnet et al 1993;DesRochers and Lieffers 2001;Fraser et al 2005Fraser et al , 2006) as a competitive strategy to impede recruitment of different species (Tarroux and DesRochers 2011). Consistently, graft formation lagged behind the outbreak by up to 7 years, suggesting that defoliation might be the underpinning trigger of graft formation in black spruce (Loehle and Jones 1990).…”
Section: Figsupporting
confidence: 52%
See 1 more Smart Citation
“…1 in Fraser et al (2006)). An attenuated effect of budworm outbreak in grafted trees supports the hypothesis that common functioning of genetically distinct individuals can overcome the death of weaker trees (Basnet et al 1993;DesRochers and Lieffers 2001;Fraser et al 2005Fraser et al , 2006) as a competitive strategy to impede recruitment of different species (Tarroux and DesRochers 2011). Consistently, graft formation lagged behind the outbreak by up to 7 years, suggesting that defoliation might be the underpinning trigger of graft formation in black spruce (Loehle and Jones 1990).…”
Section: Figsupporting
confidence: 52%
“…However, it might occur much more extensively given that it has received very little attention due to the difficulties to survey belowground tree attributes (Lev-Yadun 2011). Root connections could be beneficial under scenarios of limited carbon supply following outbreaks, as greater acquisition of resources and shared carbohydrate pools within physiologically integrated individuals (see Stone and Stone (1975) and Fraser et al (2005Fraser et al ( , 2006 and references therein) could attenuate the negative impact of defoliation in tree growth and mortality. Root grafting is gaining attention as an adaptive strategy to face disturbances and environmental hazards, as cooperative behaviour could limit tree mortality and hinder establishment of new species (Eis 1972;Tarroux and DesRochers 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Living roots on dead trees (snags) and stumps connected to living trees with a root graft are a common occurrence in many coniferous forest stands (e.g., [3,7,9,12,18]). Following the death of individual trees (either from natural causes or cutting), the base of the stem and the root systems of the remaining snags and stumps can be kept alive through the transfer of carbohydrates via root grafts from living neighbouring trees (e.g., [4,16]).…”
Section: Introductionmentioning
confidence: 99%
“…ex Loud.) was selected for this study because it has been previously shown to readily form root grafts, especially after 15 years of age [9]. Also, lodgepole pine is a shade intolerant species that has a tendency to form extremely dense single-species stands following natural disturbances [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although no tap roots existed in R-type root systems, multiple branch events caused root numbers to increase with soil depth and roots of this type performed better than other root architectures. The W-type decreased soil shear strength and their roots formed a network structure as if a skeleton of roots existed in the soil 53 . They improved soil shear strength theoretically but such an increase in strength failed to be observed because of the lack of single point measurement.…”
Section: Effects Of Root Properties and Root Architecture On Soil Shementioning
confidence: 95%